A Stochastic Analysis to Calculate the Mean Time to System Failure (MTSF) of A Two Identical Unit Parallel System - Abdulkareem, Bestun Merza (Zanco Journal of Human Sciences, 2024)
In this research two identical parallel electric generators with repair a failed one have been analyzed stochastically by two methods, first by method based on certain probability assumptions and second through three state Markov chain, classified as one recurrent ( absorbing ) state and two transient states. For the purpose of this study the data about the failure and repair time intervals of electric generators of the months november and december 2022 are obtained from the electricians of several places in Erbil city, whereas they supplied electricity to their lanes whenever the national electric power is interrupted. This research aimed to define the mean time to system failure by the two previous methods.